2010
DOI: 10.3390/ijms11010233
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effects of Supercritical Carbon Dioxide on Enzyme Activity

Abstract: Different types of enzymes such as lipases, several phosphatases, dehydrogenases, oxidases, amylases and others are well suited for the reactions in SC-CO2. The stability and the activity of enzymes exposed to carbon dioxide under high pressure depend on enzyme species, water content in the solution and on the pressure and temperature of the reaction system. The three-dimensional structure of enzymes may be significantly altered under extreme conditions, causing their denaturation and consequent loss of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 110 publications
0
57
0
Order By: Relevance
“…One of the most important is the amount of water needed to maintain their native conformation and hence, their functionality. During exposure to SC-CO 2 essential water of the enzyme can be solubilized into the SC-CO 2 (0.3 to 0.5 g water/100 g CO 2 , depending on operating pressure and temperature [7]). During the depressurization step, CO 2 is released and the solubilized water is removed from the enzyme preparation.…”
Section: Effect Of Water Content On the Residual Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important is the amount of water needed to maintain their native conformation and hence, their functionality. During exposure to SC-CO 2 essential water of the enzyme can be solubilized into the SC-CO 2 (0.3 to 0.5 g water/100 g CO 2 , depending on operating pressure and temperature [7]). During the depressurization step, CO 2 is released and the solubilized water is removed from the enzyme preparation.…”
Section: Effect Of Water Content On the Residual Activitymentioning
confidence: 99%
“…In high pressure-batch stirred reactors, exposure time, depressurization rate, and the number of pressurization/depressurization cycles are also important parameters that must be considered [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fungi failed to grow even in the presence the enrichment component such as skim milk. In previous study, Fadiloglu and Erkmen [56] showed that 84 % of the initial activity of lipase was lost after exposed for CO 2 under atmospheric pressure at initial pH 7.15 and 50 • C, while still stable in the absence of CO 2 even at 50 • C. Wimmer and Zarevúcka [57] revealed that the activity of catalase, polyphenol oxidase and peroxidase reduced by SC-CO 2 (20 MPa and 35 • C). Leitgeb et al [58] revealed that the SC-CO 2 led to inactivation of cellulase and amylase enzymes produced from Hortaea werneckii.…”
Section: Production Of Extracellular Enzymes By Fungal Spores Inactivmentioning
confidence: 96%
“…Earlier studies suggested that SC-CO 2 serves as a superior reaction environment for enzyme hydrolysis [22]. Previously, two starch-degrading enzymes, a-amylase and glucoamylase, were demonstrated to be active in a SC-CO 2 medium [23].…”
Section: Introductionmentioning
confidence: 99%